Financial managers and organizational ambidexterity in the German Mittelstand: the moderating role of strategy involvement - Christine Weigel; Klaus Derfuss; Martin R. W. Hiebl (Review of Managerial Science, 2022)
Relying on the upper-echelons perspective, this paper investigates the effect of financial managers' characteristics on the level of organizational ambidexterity reached in German Mittelstand firms. These firms are often depicted as highly innovative and able to compete on worldwide markets despite significant resource constraints. We theorize that skilled financial managers are very important in making the optimal use of Mittelstand firms' scarce resources and, in particular, for balancing exploitation and exploration, thus reaching high levels of ambidexterity. Our findings from a survey of German Mittelstand firms broadly confirm our expectations and show that financial managers' individual entrepreneurial behavior correlates positively with the firms' level of organizational ambidexterity. In addition, we find that firms with financial managers having enjoyed business education are more likely to reach high levels of ambidexterity if these financial managers are heavily involved in strategy development. Overall, these results indicate that well-suited financial managers are an important human resource for Mittelstand firms. In addition, our findings are among the first to show that financial managers not only influence finance and accounting choices, but also innovation-related outcomes such as organizational ambidexterity.
Keywords: G30; L26; M40; O32; 650; Organizational ambidexterity; Mittelstand; Financial manager; Strategy involvement